Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1089/thy.2015.0418
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism in Pregnancy: A Systematic Review and Meta-Analysis

Abstract: Background: The impact of subclinical hypothyroidism (SCH) and of levothyroxine replacement in pregnant women with SCH is unclear. The aims of this study were to assess (i) the impact of SCH during pregnancy on maternal and neonatal outcomes, and (ii) the effect of levothyroxine replacement therapy in these patients. Methods: Ovid MEDLINE In-Process & Other Non-Indexed Citations, Ovid MEDLINE, the Cochrane Controlled Trials Register, Ovid EMBASE, Web of Science, and Scopus were searched from inception to Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
210
2
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(248 citation statements)
references
References 48 publications
6
210
2
15
Order By: Relevance
“…SCH adversely affects obstetric outcomes with increasing pregnancy loss, premature delivery, and gestational hypertension (Chen et al 2014;Maraka et al 2016). On the other hand, SCH detected at the first trimester was not associated with adverse pregnancy outcomes after 20 weeks (Ong et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCH adversely affects obstetric outcomes with increasing pregnancy loss, premature delivery, and gestational hypertension (Chen et al 2014;Maraka et al 2016). On the other hand, SCH detected at the first trimester was not associated with adverse pregnancy outcomes after 20 weeks (Ong et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent review, SCH adversely affects obstetric outcomes including increasing pregnancy loss, premature delivery, and gestational hypertension (Maraka et al 2016). In contrast, it was reported that in a prospective cohort study of pregnant women, SCH at the first trimester was not associated with adverse pregnancy outcomes after 20 weeks (Ong et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Publication bias may have affected these reports, as negative studies are less likely to be published. Moreover, the vast majority of the studies assessing the impact of SCH in pregnancy are at low to moderate risk of bias, warranting less confidence in their results due to small samples, imprecision in the estimates, and failure to adjust for confounding factors (11,12).…”
mentioning
confidence: 99%
“…11 This was due to research which reported multiple maternal and neonatal adverse outcomes associated with subclinical hypothyroidism, however the role of thyroxine therapy in preventing these outcomes was unclear. 21 The American Thyroid Association in 2017 updated its guidelines for the management of thyroid disease in pregnancy following new research. Thyroxine should be given if there are antithyroid antibodies and the initial TSH is 2.5-4 mIU/L.…”
Section: Antithyroid Therapymentioning
confidence: 99%